Gold Medals, Silver Medals, Bronze Medals, and Total Medals: An Analysis of Summer Paralympic Games from 1992 to 2016 - Jacinto, Miguel (2022)
The Paralympic Games (PG) are considered one of the biggest events in the world, with increasing coverage by media and participation. The present study aimed to investigate the variation in the number of gold, silver, bronze, and totals medals in the Summer PG from 1992 to 2016. Data related to the results were extracted from the International Paralympic Committee to an SPSS database. Descriptive statistics and Friedman’s two-way analysis of variance by ranks were used to check the differences across medals in seven editions of the Summer PG, with the correspondent effect sizes. There was a peak in the maximum number of any type of medal between the 1996 and 2000 Summer PG and a decrease until 2008. After that, the number of any kind of medals has been increasing again. There were also significant differences with intermediate to large effect sizes when comparing more distant PG with more recent events. Several external factors can influence performance indicators (e.g., the number of medals) in a negative or positive way. An increase in the number of participants and a greater and better investment by the countries may explain part of our results. The preparation of an athlete must be based on a multidisciplinary team, and future organizing countries must take into account reports of previous events.